In sito galanthamine extraction during the cultivation of Leucojum aestivum L. shoot culture in two‐phase bubble column cultivation system. Issue 12 (19th September 2019) - Ivanov, Ivan; Berkov, Strahi; Pavlov, Atanas; Georgiev, Vasil
Abstract: Two‐phase bioreactor cultivation system was developed and applied for in sito recovery of extracellular galanthamine during the cultivation of Leucojum aestivum L. shoot culture in a modified column bioreactor system. The inclusion of an external circulation column with adsorbent resin Amberlite XAD‐4 as a second phase, on the 21st day of the beginning of cultivation resulted in 1.25 folds increase in biomass accumulation and maximal amounts of accumulated galanthamine of 6 mg/L (3.1 mg/L intracellular and 2.9 mg/L extracellular). It was demonstrated that the inclusion of a second phase at the cultivation of the L. aestivum shoot culture in a bubble column bioreactor with internal sections redirected the alkaloid metabolism to galanthamine synthesis and inhibits the synthesis of hemanthamine and lycorine type alkaloids. Our research demonstrated that the application of the two‐phase cultivation systems could be an important tool to increase the yields of valuable secondary metabolites in plant tissue culture‐based bioprocess.